Baseline hepatitis B core antibody predicts treatment response in chronic hepatitis B patients receiving long‐term entecavir. Issue 2 (28th November 2016) - Xu, J.‐H.; Song, L.‐W.; Li, N.; Wang, S.; Zeng, Z.; Si, C.‐W.; Li, J.; Mao, Q.; Zhang, D.‐Z.; Tang, H.; Sheng, J.‐F.; Chen, X.‐Y.; et al.
Summary: Studies regarding the clinical significance of quantitative hepatitis B core antibody (anti‐HBc) in patients with chronic hepatitis B receiving first‐line nucleos(t)ide analogues is limited. The aim of this study was to determine the performance of anti‐HBc as a predictor for hepatitis B e antigen (HBeAg) seroconversion in HBeAg‐positive CHB patients treated with entecavir. This was a retrospective cohort study consisting of 139 Chinese patients enrolled in a multicenter clinical trial treated with entecavir or entecavir maleate for up to 240 weeks. Anti‐HBc evaluation was conducted for all the available samples using a newly developed double‐sandwich anti‐HBc immunoassay. At week 240, 35 (25.2%) patients achieved a serological response (HBeAg seroconversion) and these patients at week 240 had significantly higher levels of anti‐HBc ( P <.01). We defined 4.65 log10 IU·mL −1, with a maximum sum of sensitivity and specificity, as the optimal cut‐off value of baseline anti‐HBc level to predict seroconversion. Patients with baseline anti‐HBc ≥4.65 log10 IU·mL −1 had 28.0% (26/93) and 35.5% (33/93) chance of seroconversion at weeks 144 and 240, respectively. The baseline anti‐HBc level was the strongest predictor for seroconversion at week 144 (OR: 5.78, 95% confidence interval [CI]: 2.05‐16.34, P =.001). The baseline anti‐HBc level was a strong predictor for seroconversion at week 240 (OR: 5.36, 95% CI: 2.17‐13.25, P <.001). Hence, baseline anti‐HBc titre is a useful predictor of long‐term entecavir therapy efficacy in HBeAg‐positive CHB patients, which could be used to optimize antiviral therapy.